Festival of curses: a traditional crime control method in Edo State –Nigeria (2012)
Festivals and ceremonies are part and parcel of African culture, usually in all its pump, merriment and pageantry. However, with the increasing wave of criminal activities in Nigeria especially in Edo state, festivals and ceremonies are being redefined and conceptualized in practice. Only recently a new festival ‘Festival of Curses’ was brought to the fore in combating crime in Edo state. The study therefore seeks to explain the festival as a traditional mechanism in crime control, the nature of the festival, the factors that led to its emergence in the 21st century, the level of acceptance and its impact in reducing criminal activities in the State. The study employed principally secondary literature and in-depth interviews among a cross section of the Bini. Major findings revealed that immediately after the festival of curses, a lot of criminals in the state besieged the Bini Monarch’s Palace to confess their atrocities; and pleaded for forgiveness. There was an overwhelming acceptance of the festival irrespective of the people’s religious affiliations to Christianity and Islam as a result of the potency and sudden drop in crime during the period. The study concludes that the festival should be taken as a mechanism of crime control and policing in Nigeria.